Pro powershell for amazon web services : DevOps for the AWS Cloud - Beach, Brian (Apress, 2014)
Pro PowerShell for Amazon Web Services is written specifically for Windows professionals who already know PowerShell and want to learn to host Windows workloads in the Amazon Elastic Cloud Compute (EC2) cloud service. The cloud offers information technology workers significant cost savings and agility unimaginable even just a few years ago. Tasks that traditionally took weeks of work, costing thousands of dollars, can be completed in minutes for a fraction of a penny. This book is a resource for using Microsoft's powerful scripting language, PowerShell, to create, host, manage, and administer workloads using a service widely recognized as the industry leader in cloud computing. Inside, find scripts to create and manage virtual machines, provision storage, configure networks with agility, and more--all using your preferred Windows scripting language. Use your PowerShell knowledge to harness the power of Amazon EC2 today!